Pertumbuhan dan kelangsungan hidup benih ikan Nila (Oreochromis niloticus) salin dengan pemberian pakan komersial yang berbeda - Kirikanang, Zefanya V.; Longdong, Sammy N.J; Monijung, Revol D.; Kalesaran, Ockstan J.; Kaligis, Erly Y. (Universitas Sam Ratulangi, 2022)
This study aimed to determine the growth rate and survival of saline tilapia (Oreochromis niloticus) seeds with fed with different types of commercial feed. The study was conducted at the Aquaculture Technology Laboratory in April – July 2021. The experiment was designed using a completely randomized design (CRD) with 4 treatments, each with three replications. The treatments included A: Comfeed brand feed, B: Bintang brand feed, C: Turbo Feed brand feed, D: Supra ZT brand feed. The results of the analysis of variance showed that different commercial feeds had a significant effect on absolute weight growth and specific growth, very significant for absolute length growth, but on survival rates had no significant effect. The results of the BNT test on showed absolute weight growth and specific growth showed of treatment B was not significantly different from treatment A but significantly different from treatments C and D. While for absolute length growth, treatment B was significantly different from treatments D, C, and A. Treatment D, C, and A were not significantly different from each other.